1973
DOI: 10.1029/ja078i022p04771
|View full text |Cite
|
Sign up to set email alerts
|

Particle and field observations from Explorer 45 during the December 1971 magnetic storm period

Abstract: The magnetic signatures of the extraterrestrial ring current have been measured by means of satellite‐borne magnetometers on several occasions [Smith et al., 1960; Cahill, 1966; Coleman and Cummings, 1967; Sugiura et al., 1971]. In only one case have the charged particles of the magnetic storm‐time extraterrestrial ring current system been directly observed [Frank, 1967]. In this note we present simultaneous observations from the S3‐A (Explorer 45) satellite of the magnetic signature of the ring current and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The radial dependence of the energy density plotted in Figure 4 can be used to estimate the importance of the drift mirror instability for the generation of)he Pc 5 event by this mechanism. The largest value of 0 (ratio of the proton energy density to the magnetic field energy density) measured during orbit 102 was less than 1 and occurred near apogee [Hoffman, 1973]. The criteria for satisfying the drift mirror instability condition can be expressed as [Hasegawa, 1969;Lanzerotti et al, 1969] The steep density gradient in the region L • 4.5 to L • 5.0 could also be thought to give rise to ULF waves via a drift wave mechanism [Hasegawa, 1971] Although such effects may possibly be important, it is interesting and significant to note that the simple model, neglecting such effects, can interpret the observations in an entirely consistent fashion.…”
Section: Would Suggest That Either This Is the Location Of The Disturmentioning
confidence: 94%
“…The radial dependence of the energy density plotted in Figure 4 can be used to estimate the importance of the drift mirror instability for the generation of)he Pc 5 event by this mechanism. The largest value of 0 (ratio of the proton energy density to the magnetic field energy density) measured during orbit 102 was less than 1 and occurred near apogee [Hoffman, 1973]. The criteria for satisfying the drift mirror instability condition can be expressed as [Hasegawa, 1969;Lanzerotti et al, 1969] The steep density gradient in the region L • 4.5 to L • 5.0 could also be thought to give rise to ULF waves via a drift wave mechanism [Hasegawa, 1971] Although such effects may possibly be important, it is interesting and significant to note that the simple model, neglecting such effects, can interpret the observations in an entirely consistent fashion.…”
Section: Would Suggest That Either This Is the Location Of The Disturmentioning
confidence: 94%
“…It was shown by Mauk et al [1996] This situation is very similar to the situation at Earth. Earth magnetospheric injections occur in regions where the plasma beta can be high and in the region of transition between dipolar and neutral sheet geometries [Hoffman, 1973;Williams, 1983;DeForest and Mcllwain, 1971;Kaufmann, 1987]. It is believed that the hot plasma injections are driven by energy that is stored in the form of magnetic fields and associated electric currents.…”
Section: Implications Of the Radial Distribution Of Injectionsmentioning
confidence: 99%
“…A convenient way to quantitatively illustrate the magnetic field distortions due to external current sources like the ring current is by means of the quantity AB, defined by Sugiura et al [1971] as the observed magnetic field magnitude minus the magnitude of a geomagnetic reference field. The eastward ring current lessens the effects of the westward current near the Earth so that the greatest magnetic field depression, i.e., the most negative AB values, occurs at radial equatorial distances of approximately 3 RE [Sugiura, 1972;Su and Konradi, 1975] even during magnetically active times [e.g., Hoffman, 1973]. Also, although ring current growth occurs predominately at afternoon and evening magnetic local times [e.g., Siscoe and Crooker, 1974, and references therein], the final particle and magnetic field distributions are fairly symmetric about the Earth [e.g., Smith and Hoffman, 1973] and are usually intensified relative to the initial quiet state.…”
Section: Jxb=vpmentioning
confidence: 99%